2014
DOI: 10.1177/2325967114562205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Length and Isometric Pattern of the Anterolateral Ligament With Serial Computer Tomography

Abstract: Background:Recent anatomical studies have identified the anterolateral ligament (ALL). Injury to this structure may lead to the presence of residual pivot shift in some reconstructions of the anterior cruciate ligament. The behavior of the length of this structure and its tension during range of motion has not been established and is essential when planning reconstruction.Purpose:To establish differences in the ALL length during range of knee motion.Study Design:Descriptive laboratory study.Methods:Ten unpaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 23 publications
(59 reference statements)
6
38
1
3
Order By: Relevance
“…The non-isometric pattern of the ALL is in agreement with previous in vitro studies, 1, 3, 4 and comparable length change of the ALL to our previous measurements during a quasi-static lunge were observed. 21 Helito et al 3 , found that the ALL increased in length from full extension to 90°, with greater length increase from 60° to 90° than from 0° to 60°.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The non-isometric pattern of the ALL is in agreement with previous in vitro studies, 1, 3, 4 and comparable length change of the ALL to our previous measurements during a quasi-static lunge were observed. 21 Helito et al 3 , found that the ALL increased in length from full extension to 90°, with greater length increase from 60° to 90° than from 0° to 60°.…”
Section: Discussionsupporting
confidence: 93%
“…2 These findings are directly at odds with findings by others which found the ALL to be non-isometric, and gradually increase in length during 0° to 90° of flexion, its greatest length increase was noticed from 60° to 90° of flexion. 3 Similar non-isometric behavior was found in another independent study group. 4 Possible explanations for the aforementioned differences in length change patterns might be the variability of the femoral attachment of the ALL used for ALL measurement in the cadaveric studies.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…At the time of reconstruction, in addition to the bone attachment points of the ligament on the femur and tibia and knowledge about the ALL isometricity [15], the meniscal attachment may also be important. Biomechanical studies are being conducted to test whether there is a significant function of this insertion in the genesis of anterolateral instability of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Los estudios biomecánicos sobre el LAL más recientes ponen de manifiesto el control de la estabilidad rotacional a grandes ángulos de flexión (9,18,20,21,24,(47)(48)(49) , donde no existiría un pivot shift significativo (se explora a unos 30° de flexión), mientras que otros defienden el control del mismo en extensión y escasos ángulos de flexión (1,(8)(9)(10)13,16,17) , con posibilidad de ser apreciado en el pivot shift, siendo un restrictor secundario en la estabilidad anteroposterior.…”
Section: Clínicaunclassified